Assessment of Total Costs of Ownership for Midsize Passenger Cars with Conventional and Alternative Drive Trains - Emilia Szumska; Rafal Jurecki; Marek Pawelczyk (Communications - Scientific letters of the University of Zilina, 2019)
The number of alternatively powered vehicles in Poland and EU is growing steadily. Different type of vehicle drive trains determine variations in their performances from economical and environmental technological aspects. The aim of this paper was to investigate the cost efficiency and environmental aspects of midsize passenger cars equipped with different drive train technologies: conventional, hybrid, electric and LPG fueled engine. To this purpose, the Total Cost of Ownership (TCO) method was used. Calculations were carried out by AFLEET Tool. The results show that the LPG fueled car has the lowest TCO, while the cars equipped with electric drivetrain indicate the highest TCO. However the electric car recorded the lowest cost of air pollutant emissions and externalities costs.